2010
DOI: 10.1126/science.1186624
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-Catenin Pathway Is Required for the Development of Leukemia Stem Cells in AML

Abstract: A subset of cells called leukemia stem cells (LSCs) possess limitless self-renewal and are responsible for maintenance of leukemia. Selective eradication of LSCs could offer significant therapeutic benefit and there is great interest in identifying the signaling pathways that control their development. Here, LSCs were studied in mouse models of acute myelogenous leukemia (AML) induced either by co-expression of the Hoxa9 and Meis1a oncogenes or the fusion oncoprotein MLL-AF9. We show that the Wnt/β-catenin sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
683
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 697 publications
(731 citation statements)
references
References 25 publications
23
683
3
3
Order By: Relevance
“…While there are conflicting data on the role of WNT signaling in normal hematopoietic stem cell self-renewal, mouse models have demonstrated that β-catenin is critical for AML stem cell self-renewal. [2][3][4] These data, combined with the clinical observation that increased canonical WNT signaling in AML blasts at diagnosis is associated with decreased rates of relapse-free and overall survival, suggested a potential clinical benefit for WNT suppression. 5,6 While this approach has shown promise in the treatment of AML, haematologica 2015; 100:e49 questions remain as to which subtypes of AML will benefit.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…While there are conflicting data on the role of WNT signaling in normal hematopoietic stem cell self-renewal, mouse models have demonstrated that β-catenin is critical for AML stem cell self-renewal. [2][3][4] These data, combined with the clinical observation that increased canonical WNT signaling in AML blasts at diagnosis is associated with decreased rates of relapse-free and overall survival, suggested a potential clinical benefit for WNT suppression. 5,6 While this approach has shown promise in the treatment of AML, haematologica 2015; 100:e49 questions remain as to which subtypes of AML will benefit.…”
mentioning
confidence: 93%
“…2,3 It is well known that nuclear translocation of β-catenin in this manner induces target gene transcription through physical interaction with members of the TCF/LEF family of transcription factors. While there are conflicting data on the role of WNT signaling in normal hematopoietic stem cell self-renewal, mouse models have demonstrated that β-catenin is critical for AML stem cell self-renewal.…”
mentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9][10][11] Of particular interest is the canonical Wnt pathway that has a crucial role in normal hematopoiesis and whose aberrant activation, long known to drive tumorigenesis in solid tumors, has also been involved in a number of hematological malignancies, including MCLs. 3,5,6,[12][13][14][15][16][17][18][19]20 In addition to gain-of-function mutations of intracellular components of the Wnt pathway, overexpression of Wnt receptors and ligands or downregulation of Wnt inhibitors through nongenetic modifications are also common. 3,[5][6][7]21 Short-lived response and development of resistance to first-line immunochemotherapy are major challenges in MCL and new therapeutic strategies are being developed.…”
mentioning
confidence: 99%
“…The Wnt signaling pathway is involved in the regulation of certain types of CSCs (15)(16)(17)(18)(19)(20). Additionally, the canonical Wnt signaling is activated in mammary mesenchymal subpopulation cells, but not in the parental cells, in an autocrine manner (33).…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between normal adult stem cells and CSCs suggest that the signaling pathways involved in somatic stem cell maintenance may also be involved in the regulation of CSCs. This assumption is verified in certain CSCs, such as colon (15), prostate (16) and cutaneous cancer (17), chronic myeloid leukemia (18), acute myelogenous leukemia (19) and hepatic carcinoma (20). The Wnt signaling pathway is a highly conserved signaling pathway.…”
Section: Introductionmentioning
confidence: 90%